2019
DOI: 10.1038/s41598-019-52643-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum CXCL13 reflects local B-cell mediated inflammatory demyelinating peripheral neuropathy

Abstract: Immune damages on the peripheral myelin sheath under pro-inflammatory milieu result in primary demyelination in inflammatory demyelinating neuropathy. Inflammatory cytokines implicating in the pathogenesis of inflammatory demyelinating neuropathy have been used for the development of potential biomarkers for the diagnosis of the diseases. In this study, we have found that macrophages, which induce demyelination, expressed a B-cell-recruiting factor CXC chemokine ligand 13 (CXCL13) in mouse and human inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…However, the correlation of CXCL13 serum levels with the number of CXCL13-positive cells within the MSG inflammatory lesions found in this study and with various histologic parameters, including the degree of MSG inflammation and the presence of eGCs, shown in this and previous studies (24,26,29), suggest that at least a part of the elevated CXCL13 serum levels in pSS patients arise from the affected salivary glands. This is in agreement with previous findings linking local and systemic autoimmune responses in pSS (33,52,53), as well as relevant findings in other autoimmune diseases suggesting that CXCL13 serum levels reflect the local inflammation in the affected organs (18,54). On the other hand, we have previously observed that the number of infiltrating FDCs in MSG lesions of pSS patients decreases in more severe lesions (33).…”
Section: Discussionsupporting
confidence: 93%
“…However, the correlation of CXCL13 serum levels with the number of CXCL13-positive cells within the MSG inflammatory lesions found in this study and with various histologic parameters, including the degree of MSG inflammation and the presence of eGCs, shown in this and previous studies (24,26,29), suggest that at least a part of the elevated CXCL13 serum levels in pSS patients arise from the affected salivary glands. This is in agreement with previous findings linking local and systemic autoimmune responses in pSS (33,52,53), as well as relevant findings in other autoimmune diseases suggesting that CXCL13 serum levels reflect the local inflammation in the affected organs (18,54). On the other hand, we have previously observed that the number of infiltrating FDCs in MSG lesions of pSS patients decreases in more severe lesions (33).…”
Section: Discussionsupporting
confidence: 93%
“…Measuring CXCL13 concentration in the CSF could be a clinical adjunct to discriminate ALS from other neurological diseases. This because, unlike ALS, CXCL13 dramatically increased in the CSF of patients with other inflammatory diseases such as encephalitis [66], chronic inflammatory demyelinating polyneuropathy [67], MS [26,68], LMN [51] or rheumatoid meningitis [69].…”
Section: Discussionmentioning
confidence: 99%
“…SC transdifferentiation to DSCs has been recently suggested to be involved in inflammatory demyelinating neuropathies [ 33 ]. We thus examined whether a similar alteration in autophagy is induced during demyelination in EAN, a rat model of inflammatory demyelinating neuropathy [ 18 ]. The levels of p62 were found to be increased in the SCs of EAN rats compared to those of control rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Female rats aged 7–12 weeks and weighing 160–200 g were used. Active EAN was induced in the rats as described previously [ 18 ]. Briefly, each rat was injected in both hind footpads with an emulsion containing 100 mg SP-26, a neuritogenic peptide homologous to amino acids 53–78 of bovine myelin P2 protein (Shimadzu), and Freund’s complete adjuvant (Sigma-Aldrich, F5881; M. tuberculosis H37Ra, 5 mg/mL).…”
Section: Methodsmentioning
confidence: 99%